The Effect of Heating on Accorbate Acid Levels (Acidum Ascorbicum) Invitamin C Planar Joints That Spread in Jambi's Pharmacy by Iodatometry Method - Hisran H; Salmah Salmah (Jurnal Health Sains, 2024)
Ascorbic acid (Acidum ascorbicum) is an active component of vitamin C planar joints that spread in Jambi City. The planar jointsform is more than the tablet. Ascorbic acid can turn into an inactive form because it is easily oxidized and accelerated by heat, this research was done to know the effect of heating ascorbic acid content. This research was used three types of vitamin C samples (2 tablets and 1 solution) were obtained randomly from three different pharmacies. Samples were given a heating treatment of 300 C, 600 C, 800 C and 1000C each at 0, 60, 120 and 180 minutes with 3 repetitions and vitamin C levels were known to use the Iodatometric titration method. The highest vitamin C tablet content was found in preparations heated at 300C with the percentage of sample I = 99.8%, sample II = 96.3% and sample 3 = 90.17%. The lowest vitamin C content was carried out at 1000C with the percentage of sample I = 74.6% and sample II = 74.4% and sample 3 = 70.2%. The statistical test results show the value of sig. smaller than 0.05, it is means that there are differences the result of heating effect from three samples tested.